2019
DOI: 10.1111/vsu.13278
|View full text |Cite
|
Sign up to set email alerts
|

Effects of needle gauge and syringe size on small intestinal leakage at injection sites

Abstract: Objective To determine the influence of needle gauge, syringe volume, and syringe size on needle tract leakage after injection in porcine jejunum. Study design Ex vivo experiment. Sample population Three hundred sixty jejunal segments from 20 feedlot pigs. Methods Fresh porcine intestines were divided into 5‐cm or 10‐cm segments and randomly assigned to the one of nine treatment groups: 25‐gauge, 22‐gauge, and 20‐gauge needles attached to full 12‐mL, half‐full 20‐mL, and full 20‐mL syringes (n = 20/group). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Recently, Brand et al reported that use of a 22 gauge needle for saline infusion minimized leakage from the transmural defect, while use of a 25 gauge needle increased the risk of leakage. 33 They proposed that the surgeon had to generate greater pressure to infuse the saline through the 25 gauge needle, resulting in greater micromotion of the needle at the transmural defect and "coring" of the intestinal wall. While a larger, 18 gauge, IV catheter was used in the present study, leakage was not observed from the catheter site in any enterotomy constructs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Brand et al reported that use of a 22 gauge needle for saline infusion minimized leakage from the transmural defect, while use of a 25 gauge needle increased the risk of leakage. 33 They proposed that the surgeon had to generate greater pressure to infuse the saline through the 25 gauge needle, resulting in greater micromotion of the needle at the transmural defect and "coring" of the intestinal wall. While a larger, 18 gauge, IV catheter was used in the present study, leakage was not observed from the catheter site in any enterotomy constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the present study established and validated a protocol for intraluminal air insufflation of the small intestine, which may be used for future cadaveric studies or even adapted for intraoperative use. Recently, Brand et al reported that use of a 22 gauge needle for saline infusion minimized leakage from the transmural defect, while use of a 25 gauge needle increased the risk of leakage 33 . They proposed that the surgeon had to generate greater pressure to infuse the saline through the 25 gauge needle, resulting in greater micromotion of the needle at the transmural defect and “coring” of the intestinal wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a plastic manometer over a pressure transducer for LT, as this is an affordable easily sterilizable instrument 26 . Our assistant injected fluid manually 26–28 rather than using a syringe pump, despite possible resulting fluctuations in fluid rate administration, to closely mimic a clinical scenario. However, we did not use 18G catheters through the intestinal wall for LT as done by other investigators, which would have better mirrored the clinical setting 12,14,26,27,40,45 .…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple intraoperative techniques reported to assess for gaps or leaks between suture bites in veterinary medicine, including milking ingesta across an anastomosis 2,23 or injecting saline to identify leaks from the suture line 1,2,4,18,26–28 . In a 2019 literature review, Ellison et al recommended performing leak testing (LT) for all intestinal closures 29 .…”
Section: Introductionmentioning
confidence: 99%